Exploration of the Factors of Work Readiness during the Pandemic COVID-19 - Laili Qomariyah; Mariza Ningtyas Febriyanti (Proceedings Series on Social Sciences & Humanities, 2021)
This study aims to develop a work readiness theory during pandemics based on existing theories and data obtained in the field. The research approach used is a qualitative method with a grounded theory approach. Research subjects are parties who have an interest and are involved in job readiness, namely managers, employees, recruiters, and educators. There are fifteen subjects in this research. Data analysis was carried out in 4 stages: open coding, focused coding, axial coding, and selective coding to organize and integrate categories into a single category. Validation of this study was carried out by triangulation, namely by validating respondents. The researcher re-interviewed the participants by questioning the results of previous interviews to see the consistency of the data obtained. The results showed that five factors correlate with each other. The first is social support which includes support from the school environment, parents, and friendship. The second factor is the internal force which functions as a driving force for individuals to carry out a behavior. The third is the opportunity aspect. The fourth is the competency that includes how to work attitude of fresh graduates and their digital mindset. Individuals are ready to work if competence and persistence in the search can be carried out correctly. And the last selection readiness is about readiness to understand their position. This research is expected to become additional information for the future as an initial source in developing studies related to the work readiness of graduates. The study results show that it takes both internal and external strength to prepare fresh graduates for work.